Insulinoma in childhood: a retrospective review of 22 patients from one referral centre - Melikyan, Maria; Gubaeva, Diliara; Shadrina, Anna; Bolmasova, Anna; Kareva, Maria; Tiulpakov, Anatoly; Efremenkov, Artem; Sokolov, Yuri; Brusgaard, Klaus; Christesen, Henrik T.; Andersen, Kirstine; Stepanov, Alexey; et al. (Frontiers in Endocrinology, 2023)
Background: Insulinomas are very rare in childhood with sparse knowledge on the clinical aspects and the presence of Multiple Endocrine Neoplasia type 1 (MEN1). Methods: We conducted a retrospective review of patients diagnosed with insulinoma between 1995 and 2021, presenting to one referral centre in Russia. Clinical, biochemical, genetic, imaging and histological data were collected. In addition, follow-up and family data were obtained. Results: A total of twenty-two children aged 5 to 16 years were identified. The median (range) gap between the first hypoglycaemia symptoms and diagnosis was 10 (1-46) months. Twelve children (55%) were misdiagnosed to have epilepsy and were treated with anticonvulsants before hypoglycemia was revealed. Contrast enhanced MRI and/or CT were accurate to localize the lesion in 82% (n=18). Five patients (23%) had multiple pancreatic lesions. All children underwent surgical treatment. The median (range) diameter of removed tumors was 1.5 (0.3-6) cm. Histopathological studies confirmed the presence of insulinoma in all cases. Immunohistochemical studies revealed G2 differentiation grade in 10 out of 17 cases. Two patients were diagnosed with metastatic insulinoma. One of them had metastases at the time of insulinoma diagnosis, while the other was diagnosed with liver metastases eight years after the surgery. Eight children (36%) were found to carry MEN1 mutations, inherited n=5, de novo n=1, no data, n=2. Children with MEN1 had significantly higher number of pancreatic tumors compared to sporadic cases. All of them developed additional MEN1 symptoms during the following 2-13 years. In the five patients with inherited MEN1, seven family members had hitherto undiscovered MEN1 manifestations. Conclusions: In this large cohort of children with rare pediatric insulinomas, MEN1 syndrome and G2 tumors were frequent, as well as hitherto undiscovered MEN1 manifestations in family members. Our data emphasize the need of genetic testing in all children with insulinoma and their relatives, even in the absence of any other features, as well as the importance of a prolonged follow-up observation.